1979
DOI: 10.1111/j.1399-3054.1979.tb02626.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glyphosate on Metabolism of Phenolic Compounds

Abstract: Light enhanced the inhibiting effect of root-fed glyphosate (5 x l'0~* M) on dry weight accumulation of soybean [Glycine max, (L.) Merr.l seedling axes. Inhibition of growth by iight 'was greatest in hypocotyls, whereas by glyphosate it was greatest in roots. A synergistic effect of light and glyphosate on stimulation of phenylalanine ammonia-lyase (PAL, B.C. 4.3.1.5) activity was also demonstrated. In continuous white light PAL activity increased linearly for 4 days in axes of seedlings exposed to glyphosate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
3

Year Published

1981
1981
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 39 publications
3
43
3
Order By: Relevance
“…This inhibition led to decreased levels of aromatic amino acids that subsequently cause an inhibition of protein synthesis Rubin et al, 1984). In addition, glyphosate induced high levels of PAL activity (Duke et al, 1979(Duke et al, , 1980Cooley and Foy, 1992;Amrhein and Gödeke, 1977). High levels of PAL activity produced toxic levels of ammonia and increased the levels of growth-inhibiting phenolic compounds (Duke et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This inhibition led to decreased levels of aromatic amino acids that subsequently cause an inhibition of protein synthesis Rubin et al, 1984). In addition, glyphosate induced high levels of PAL activity (Duke et al, 1979(Duke et al, , 1980Cooley and Foy, 1992;Amrhein and Gödeke, 1977). High levels of PAL activity produced toxic levels of ammonia and increased the levels of growth-inhibiting phenolic compounds (Duke et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Control (mol%) Glyphosate (mol%) important precursor in the production of IAA (Hoagland et al, 1978;Duke et al, 1979). Thus, the effect of glyphosate on aromatic amino acid metabolism was the next examination.…”
Section: Amino Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…Gresshoff (12) reported reversal of glyphosate inhibition of Arabidopsis thaliana seedlings with a combination of phenylalanine and tyrosine. In contrast, Duke and Hoagland (6) observed increased inhibition by glyphosate of corn seedling growth when phenylanine and tyrosine were added.Several studies (7,8,16) show that glyphosate treatment can decrease free phenylalanine and tyrosine levels. Recent studies have indicated that glyphosate inhibits the synthesis of flavonoids and chlorogenic acid in buckwheat hypocotyls (17) and causes an accumulation of shikimate that is significantly correlated with a…”
mentioning
confidence: 99%